Electronic health services for cardiac patients: a salutogenic approach - Lahtiranta, Janne; Koskinen, Jani (Finnish Journal of eHealth and eWelfare, 2013)
Patient‐centricity is a name given to the on‐going transformation in health care delivery. The term is widely used and it has been given different interpretations in relation to the context of its use. These interpretations emphasize aspects such as empowerment, seamless chain of care, and even responsibility; how it is divided amongst the service provider and the patient. Regardless of the interpretation and the context of use, one thing is constant; a genuine desire to support the patient’s health related endeavours in a field that is fragmented and becoming increasingly technology‐oriented. In order to support the patient in this field, a comprehensive approach to health is needed to capture nuances of everyday life outside singular health related transactions (such as appointments, laboratory visits, etc.) and technology. This article looks into some well‐established theories used in depicting such a comprehensive view to health and well‐being, and conceptualizes their applicability to real‐world electronic health services. The article reports preliminary results in the form of proposed new functions, ideas on the applicability of the theories and describes the outline of the iterative development process. The findings of this article base on development of electronic health services for cardiac patients performed in an on‐going project, which is executed during 2011–2013.